An Eternal Planting, A House of Holiness: The Self-Understanding of the Dead Sea Scrolls Community - Swarup, Paul N. W. (Tyndale bulletin, 2003)
A dissertation examining two metaphors, 'an eternal planting' and ‘a house of holiness’, which were used extensively by the DSS community in expression of their self-understanding.